Formation of core–shell structure from carbon nanotube and gold nanowire: a molecular dynamic simulation. Issue 5 (7th April 2022) - Yang, Shengye; Zhang, Danhui; Liang, Ruquan; Song, Yuanmei; Shi, Jianhui; Yang, Houbo; Liu, Anmin
Abstract: Molecular dynamics simulations are used to investigate the interaction between the carbon nanotubes (CNTs) and gold (Au) nanowires (NWs). From the result, it can be seen that when the CNT places beside the Au NW, the CNT is gradually close to Au NW, and then collapse, self-scroll onto the Au NWs, finally form a coaxial core–shell nanocomposite. It is also found that the van der Waals force plays a decisive role in this process. Furthermore, the diameter of the CNT and the cross-section of the Au NWs also affect the fabrication process. Moreover, the interaction between multi-walled carbon nanotube and Au nanowires was also discussed in detail. Graphical abstract: UF0001